2010
DOI: 10.4049/jimmunol.1000690
|View full text |Cite
|
Sign up to set email alerts
|

IL-2 and IL-4 Stimulate MEK1 Expression and Contribute to T Cell Resistance against Suppression by TGF-β and IL-10 in Asthma

Abstract: The T cell-driven airway inflammation in chronic asthma is uninhibited and sustained. We examined the resistance of T cells from asthmatic patients against suppression by TGF-β, IL-10 and glucocorticoids and explored its signaling mechanism. CD4+CD25− T cells from allergic asthmatic subjects demonstrated increased TCR-stimulated proliferation as compared with healthy and chronic obstructive pulmonary disease controls. This proliferation was resistant to inhibition by TGF-β, IL-10, and dexamethasone and to aner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
2
24
0
1
Order By: Relevance
“…24, 31, 32 This pathway induces the activating protein 1 (AP1) transcription factors, which antagonize glucocorticoids. Conversely, glucocorticoids antagonize AP1 by inducing GILZ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…24, 31, 32 This pathway induces the activating protein 1 (AP1) transcription factors, which antagonize glucocorticoids. Conversely, glucocorticoids antagonize AP1 by inducing GILZ.…”
Section: Resultsmentioning
confidence: 99%
“…33 We have previously reported that CD4 T cells from moderate to severe asthmatic patients have increased expression of MEK1. 24 Inhibition of MEK1 reverses T cell resistance against dexamethasone. We analyzed BAL CD4 T cells for MEK1 (referred to as MEK) expression and the sensitivity of MEK positive cells to dexamethasone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further correlation analysis of the polymorphism at −589 and the levels of IL-4 and total IgE show no correlation between them. Asthma is a complex disease, and apart from the many immunocytes and their cytokines that cause this disease (Bottema et al, 2010;Karwot et al, 2008;Liang et al, 2010;Xu et al, 2010), other factors affect IL-4 and total IgE levels.…”
Section: Discussionmentioning
confidence: 99%